2012
DOI: 10.1016/j.ejmech.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of carbocyanine dyes as PRMT inhibitors and imaging agents

Abstract: Summary Protein arginine methylation regulates multiple biological processes. Deregulation of protein arginine methyltransferase (PRMT) activities has been observed in many disease phenotypes. Small molecule probes that target PRMTs with strong affinity and selectivity can be used as valuable tools to dissect biological mechanisms of arginine methylation and establish the role of PRMT proteins in a disease process. In this work, we report synthesis and evaluation of a class of carbocyanine compounds containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…In a general procedure, the radioisotope-labeled methyl group from [ 3 H]-SAM or [ 14 C]-SAM is first enzymatically transferred into a peptide or protein substrate of PRMTs. Prior to quantitation by autoradiography or liquid scintillation counting, the methylated substrates have to be separated from unreacted SAM by using different approaches such as polyacrylamide gel electrophoresis (radiometric gel assay, RGA) [7076], pipette chromatography (ZipTip assay) [77], and filtering on glass fiber or phosphocellulose paper discs (radiometric filter assay, RFA) [37, 73, 7890]. To eliminate the washing step required for the above described radiometric assays, scintillation proximity assay (SPA) has been implemented [80, 91101], in which the scintillation signals depend on the micrometer proximity between biotinylated substrates and streptavidin-coated scintillants (either FlashPlates or streptavidin-coated microscopic beads).…”
Section: Biochemical Assays In Prmt Inhibitor Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In a general procedure, the radioisotope-labeled methyl group from [ 3 H]-SAM or [ 14 C]-SAM is first enzymatically transferred into a peptide or protein substrate of PRMTs. Prior to quantitation by autoradiography or liquid scintillation counting, the methylated substrates have to be separated from unreacted SAM by using different approaches such as polyacrylamide gel electrophoresis (radiometric gel assay, RGA) [7076], pipette chromatography (ZipTip assay) [77], and filtering on glass fiber or phosphocellulose paper discs (radiometric filter assay, RFA) [37, 73, 7890]. To eliminate the washing step required for the above described radiometric assays, scintillation proximity assay (SPA) has been implemented [80, 91101], in which the scintillation signals depend on the micrometer proximity between biotinylated substrates and streptavidin-coated scintillants (either FlashPlates or streptavidin-coated microscopic beads).…”
Section: Biochemical Assays In Prmt Inhibitor Studymentioning
confidence: 99%
“…We recently screened a serial carbocyanine compounds against PRMT1 using the RFA assay [78], among which compound 11 was discovered with promising potency (IC 50 = 4.1 μM) compared to AMI-1 and compound 13 ( stilbamidine) (137 μM and 105 μM, respectively, determined under the same assay condition [89]). This compound also inhibits PRMT3, -5 and -6 with slightly weaker potency but is totally inactive to CARM1.…”
Section: Prmt1-specific Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Purandare et al identified a series of pyrazole amide containing compounds as potential inhibitors through high-throughput screening; preliminary optimization of these compounds led to Methylgene compound 7a ( [95,96]. It is also worth mentioning the carbocyanine inhibitors developed by Sinha et al, which are not only selective PRMT1 inhibitors (Table 17.1, entry 41, IC50 5 4.1 6 0.1) but also a photoactive chemical probe for the further study and characterization of PRMT inhibitors [98]. It is also worth mentioning the carbocyanine inhibitors developed by Sinha et al, which are not only selective PRMT1 inhibitors (Table 17.1, entry 41, IC50 5 4.1 6 0.1) but also a photoactive chemical probe for the further study and characterization of PRMT inhibitors [98].…”
Section: Prmt Inhibitorsmentioning
confidence: 99%
“…High-resolution accurate mass spectra (HRMS) were obtained either at the Georgia State University Mass Spectrometry Facility using a Waters Q-TOF micro (ESI-Q-TOF) mass spectrometer or utilizing a Waters Micromass LCT TOF ES+ Premier Mass Spectrometer (Waters Corporation, Milford, MA, USA). The synthetic procedures for the preparation of 1, 2, and 3 have been previously reported by our lab [15,16].…”
Section: Synthesismentioning
confidence: 99%